Quality of Life in a Dynamic Spatial Model - Gabriel Ahlfeldt; Fabian Bald; Duncan Roth; Tobias Seidel (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We develop a dynamic spatial model in which heterogeneous workers are imperfectly mobile and forward-looking and yet all structural fundamentals can be inverted without assuming that the economy is in a stationary spatial equilibrium. Exploiting this novel feature of the model, we show that the canonical spatial equilibrium framework understates spatial quality-of-life differentials, the urban quality-of-life premium and the value of local non-marketed goods. Unlike the canonical spatial equilibrium framework, the model quantitatively accounts for local welfare effects that motivate many place-based policies seeking to improve quality of life.
Keywords: J20; J30; R20; R30; R50; 330; Covid; dynamic; housing; migration; rents; pollution; productivity; spatial equilibrium; quality of life; wages; welfare